Streaming Science #2: Using Webcast Electronic Field Trips for Engagement with Your Target Audience: WC417/AEC756, 4/2022 - Loizzo, Jamie; Beattie, Peyton; Kent, Kevin (EDIS, 2022)
This is the second publication in the Streaming Science EDIS series focused on how to use mobile hardware and software for engagement with your target audience. This new 6-page article focuses on how to use mobile hardware and cloud-based software for streaming live webcast electronic field trips (EFTs). Streaming Science utilizes EFTs to connect university scientists and Extension professionals across a variety of subject matter areas and contexts with PK–12 students around the world. Written by Jamie Loizzo, Peyton Beattie, and Kevin Kent, and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc417